Crimes against humanity: evolution, prosecution, and challenges for the International Criminal Court - Pillai, Aneesh V. (International e-journal of criminal sciences, 2024)
In international law, the term crimes against humanity refers to crimes, including murder, torture, enforced disappearance, etc., committed in a large-scale manner against civilians irrespective of their nationality. The crimes against humanity, together with crimes such as genocide, war crimes, and crimes against aggression, form part of core crimes in international criminal law. The idea of crimes against humanity traces its development to the early 1900s, and subsequently, it received serious attention during the Second World War. The Agreement for the Prosecution and Punishment of the Major War Criminals of the European Axis, adopted in 1945, has defined the term crimes against humanity for the first time in its history. Subsequently, several developments occurred, including the Nuremberg Trials, the Tokyo Trial, the International Criminal Tribunal for Former Yugoslavia and the International Criminal Tribunal for Rwanda, etc. All these have significantly influenced the moulding of crimes against humanity. Finally, adopting the Statute of the International Criminal Court has given a final shape to the concept of crimes against humanity and the methods to deal with its prosecution, punishment, etc. Being one of the core international criminal law crimes, this paper examines the historical evolution, the concept of crimes against humanity and the various criticisms and challenges in prosecuting crimes against humanity under international criminal law.